Brain mediators of systemic oxidative stress on perceptual impairments in Parkinson's disease. Issue 1 (December 2015) - Lin, Wei-Che; Chou, Kun-Hsien; Lee, Pei-Lin; Huang, Yung-Cheng; Tsai, Nai-Wen; Chen, Hsiu-Ling; Cheng, Kuei-Yueh; Wang, Hung-Chen; Lin, Tsu-Kung; Li, Shau-Hsuan; Chen, Meng-Hsiang; Lu, Cheng-Hsien; et al.
Abstract Background Parkinson's disease (PD) is well documented to be associated with elevated systemic oxidative stress and perceptual impairments. Furthermore, the striatum and extrastriatal cortical areas, which are involved in the coordination of perceptual functions, are impaired at an early stage of the disease. However, the possible pathophysiology involved in perceptual impairments remains unclear. This raises the possibility that structural abnormalities might mediate the relationship between oxidative stress and perceptual impairments. Methods We explored the differences between 27 patients with PD and 25 healthy controls in terms of serum oxidative stress, perceptual functions, and regional gray matter. A single-level three-variable mediation model was used to investigate the possible relationships between serum oxidative stress, regional gray matter volume, and different domains of perceptual functioning. Results The results demonstrate that increased serum oxidative stress (as indicated by thiobarbituric acid reactive substances) was associated with declined perceptual functioning in PD patients. We further explored significant gray matter volume reductions in the bilateral temporal gyri (middle temporal gyrus and fusiform gyrus), bilateral frontal gyri, limbic lobe (hippocampus and uncus), left inferior parietal lobule, right caudate nucleus, and insula in PD. Further mediation analysis showed that gray matter volumes in the middle temporal gyrus, inferior parietal lobule, hippocampus, and insula served as brain mediators between elevated serum oxidative stress and perceptual impairments. Conclusions These results suggest that higher oxidative stress levels adversely impact perceptual functions by causing temporal and mesolimbic abnormalities.